Інновації та управління якістю в технології традиційного і органічного печива з цільнозерновим жорновим борошном - Камбулова, Юлія Вікторівна; Кохан, Олена Олександрівна; Ворвихвост, Андрій Миколайович; Янюк, Тетяна Іванівна; Фалендиш, Наталія Олексіївна; Гоменюк, Катерина Анатоліїівна (My University, 2025)
У статті наведено результати досліджень показників якості цільнозернового жор¬нового пшеничного, спельтового, ячмінного, амарантового борошна і борошна зе¬леної гречки з метою застосування його в технології печива. З’ясовано, що наяв¬ність клітковини і вища його крупність порівняно з пшеничним борошном вищого сорту не забезпечують необхідних в’язко-пластичних характеристик тіста для здобного печива, що потребує корегування. Встановлено доцільність введення глюкоамілази та целюлази, які гідролізують складні вуглеводи до глюкози, покра¬щуючи його структуру. Органолептичні показники тіста і готової продукції обу¬мовлюються видом конкретного зерна. The article presents the results of research on the quality indica¬tors of whole grain stone-ground wheat, spelt, barley, amaranth flo¬ur, and green buckwheat flour for use in cookie production. It has been established that whole grain flour has organoleptic properties characteristic of a particular type of grain and differs significantly from high-grade wheat flour. In terms of whiteness, spelt and bar¬ley samples are the lightest, while wheat and amaranth flour are the dar-kest. The granulometric composition of stone-ground whole grain flo¬ur is heterogeneous. The size of the main fraction of amaranth and wheat stone-ground flour ranges from 200 to 150 microns, for green buckwheat and barley flour — over 200 microns and within 132—150 microns, respectively, and for spelt flour — over 200 to 150 μm. Among the samples studied, only whole grain wheat and spelt flour form a gluten complex under standard washing conditions. At the same time, the amount of gluten extracted from them is lower than that from premium wheat flour — by 34.5% for whole wheat and by 24.5% for spelt. The elasticity of the gluten in both samples is rated as good. The gluten of whole wheat flour belongs to group I according to the IDC and is also characterized as good, but due to the presence of dietary fiber, its extensibility is 10% lower than that of premium wheat flour gluten. Spelt flour gluten belongs to quality group II, but demonstrates 6.7% higher elasticity compared to wheat flour. In stone-ground flour made from barley, buckwheat, and amaranth, gluten structure does not form. Dough for shortbread cookies made from stone-ground whole grain flour does not have typical viscous-plastic properties, but these characteristics can be improved by adding hydrolytic enzymes. The feasibility of introducing glucoamylase and cellulase, which hydro-lyze complex carbohydrates to glucose, improving its structure, has been established. The most effective was the combined use of both enzymes, which reduced the fermentation time by 2—4 hours com¬pared to their separate use.
Keywords: кафедра технології хлібопекарських і кондитерських виробів; кафедра технології зберігання і переробки зерна; жорновий помел; печиво; ферменти; глюкоамілаза; целюлаза; whole grain flour; stone grinding; cookies; enzymes; glucosidase; glycoamylase; cellulase